2008
DOI: 10.1590/s0103-84782008000200001
|View full text |Cite
|
Sign up to set email alerts
|

Extratos, decoctos e óleos essenciais de plantas medicinais e aromáticas na inibição de Glomerella cingulata e Colletotrichum gloeosporioides de frutos de goiaba

Abstract: A principal doença da goiaba (Psidium guajava L.), após a colheita, é a antracnose, causada por Glomerella cingulata e Colletotrichum gloeosporioides. Estes patógenos e o resíduo de fungicidas em frutos são considerados os principais problemas para a exportaçãodesta fruta. Neste trabalho, foi avaliado o efeito fungitóxico de extratos, decoctos e óleos essenciais de plantas medicinais e aromáticas, no crescimento micelial dos patógenos, in vitro, recomendados como alternativa para o controle químico em pós-colh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
36

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 6 publications
2
22
0
36
Order By: Relevance
“…Ribeiro & Bedendo (1999) observed a reduction of 67.57% in mycelial growth working with A. sativum extract at 1%. Rozwalka et al (2008) observed that C. gloeosporioides can be affected by aqueous extracts of Rosmarinus officinalis L., Zingiber officinale Rosc., Chamomila recutita L. and S. aromaticum at a concentration of 10% with 50.57%, 64.37%, 73.56% and 100% of mycelial growth inhibition.…”
Section: Influence Of Extracts On the Mycelial Growth Of Etiologic Agmentioning
confidence: 99%
“…Ribeiro & Bedendo (1999) observed a reduction of 67.57% in mycelial growth working with A. sativum extract at 1%. Rozwalka et al (2008) observed that C. gloeosporioides can be affected by aqueous extracts of Rosmarinus officinalis L., Zingiber officinale Rosc., Chamomila recutita L. and S. aromaticum at a concentration of 10% with 50.57%, 64.37%, 73.56% and 100% of mycelial growth inhibition.…”
Section: Influence Of Extracts On the Mycelial Growth Of Etiologic Agmentioning
confidence: 99%
“…camara, belonging to the Verbenaceae family, exhibits antimicrobial activity (DEENA;THOPPIL, 2000), efficacy against termite workers (VERMA; VERMA, 2006) and has a nematostatic effect on the phytonematode Meloidogyne incognita (DIAS et al, 2000). T. minuta, from the Asteraceae family, has fungitoxic effects (ROZWALKA et al, 2008), activity against Anopheles stephensi larvae (HADJIAKHOONDI et al, 2005), antibacterial activity (SOUZA et al, 2000) and effect on H. contortus egg and larvae (MACEDO et al, 2012). A. zerumbet, from the Zingiberaceae family, exhibits antioxidant (ELZAAWELY et al, 2007), antibacterial and antifungal activities (VICTÓRIO et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Em laboratório, foi avaliado o efeito fungitóxico de algumas plantas medicinais e aromáticas, entre elas, a camomila, acreditando que poderia haver alguma ação contra os fungos Glomerella cingulata e Colletotrichum gloeosporioides, causadora da antracnose em goiaba (Psidium guajava L.). Constatou-se que a camomila, preparada em decocto, deteve grande controle biológico de C. gloeosporioides, indicando sua aplicação como controle alternativo contra antracnose (ROZWALKA, 2008).…”
Section: Resultsunclassified